Strategi Pengembangan Website Organisasi SMA Islam Hidayatullah dengan Metode Design Thinking - Robbie Adam Nurdiansyah; Jeffri Alfa Razaq; Dwi Budi Santoso (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study developed the SMA Islam Hidayatullah website using the Design Thinking method to enhance student engagement and improve the communication efficiency of school organizations such as OSIS, Rohis, DA, Askar, and PMI. The method involved the stages of Empathize, Define, Ideate, Prototype, and Test, engaging collaboration between students, organization members, and teachers to understand and meet user needs. The results demonstrate that the Design Thinking approach is effective, with the website offering interactive features such as discussion forums, event calendars, and multimedia galleries. The website successfully increased student engagement, as evidenced by improved interaction among students, and enhanced communication among members by improving the quality and efficiency of information shared. The implications of using Design Thinking show that this approach creates solutions better aligned with user needs and enhances their satisfaction and involvement. Recommendations include developing additional features such as instant messaging, user training, and regular monitoring to ensure the website’s maximum benefits. The use of Design Thinking has proven to provide better solutions in school website development, improving student engagement and organizational communication efficiency.